Development and Validation of the Knowledge and Attitude Scale Toward COVID-19 Pandemic Breaking Transmission Chain (KA-C) Among Iranian Population - Abounoori, Mahdi; Maddah, Mohammad Moein; Sharif Nia, Hamid; Rahmatpour, Pardis; Khosravifar, Shaghayegh; SamadiKouchaksaraei, Mohammad; Khosravifar, Shahrzad (Frontiers in Public Health, 2021)
Objectives We aimed to develop and evaluate the scale's validity and reliability to measure factors affecting people's knowledge and attitudes toward the pandemic breaking transmission chain. Methods This exploratory mixed-method study was carried out in two phases: 1) item generation with literature review and interviews and,2) item reduction by psychometric assessments of developed scale. The face, content, construct (exploratory and confirmatory factor analysis), convergent, and discriminant validity of the scale were assessed in the Iranian population (n=500) from March to June 2020. The Composit Reliability(CR) and the internal consistency correlation coefficient were estimated. Results The Knowledge and Attitude Scale Toward COVID-19 Pandemic Breaking Transmission Chain (KA-C) among the Iranian population included 18 items. Two factors with a whole variance of 66.05% identified by exploratory factor analysis. Factors were labeled as "health literacy" and "home health empowerment." The confirmatory factor analysis showed the goodness of fit. The CR of the scale for first and second factors were .965 and .833 receptively. The scale's internal consistency correlation coefficient was acceptable. (Cronbach's alpha =0.960 and 0.823, average interitem correlation =0.643 and 0.635, McDonald's omega =0.963 and 0.829, for the first and second factor, receptively). Conclusion The KA-C scale can be exerted to screen the people's knowledge and attitude about the COVID-19 pandemic breaking the transmission chain as a valid and reliable scale for further policymaking, health care provides, and multi-dimensional psychosocial assessment of the pandemic period.